Edge computing : fundamentals, advances and applications - Kumari, K. Anitha; Sadasivam, G. Sudha; Dharani, D.; Niranjanamurthy, M. (Boca Raton, FL : CRC Press, 2022)
"This reference text presents the state-of-the-art in edge computing, its primitives, devices and simulators, applications, and healthcare-based case studies. The text provides integration of blockchain with edge computing systems and integration of edge with Internet of Things (IoT) and cloud computing. It will facilitate the readers to setup edge-based environment and work with edge analytics. It covers important topics including cluster computing, fog computing, networking architecture, edge computing simulators, edge analytics, privacy-preserving schemes, edge computing with blockchain, autonomous vehicles, and cross-domain authentication. Aimed at senior undergraduate, graduate students and professionals in the fields of electrical engineering, electronics engineering, computer science, and information technology, this text: Discusses edge data storage security with case studies and blockchain integration with edge computing system. Covers theoretical methods with the help of applications, use cases, case studies, and examples. Provides healthcare real-time case studies are elaborated in detailed by utilizing the virtues of homomorphic encryption. Discusses real-time interfaces, devices, and simulators in detail"--
OCLC-licensed vendor bibliographic record.
Keywords: Edge computing; COMPUTERS / Computer Engineering; COMPUTERS / Computer Science